Electrical load management in industrial and commercial sectors : case of Nepal - Rajbhandari, Surendra; Edelman, David J.; Shrestha, Ram M.; Zhai Youg-Ping; Government of Australia (Bangkok : Asian Institute of Technology, 1991)
Until recently, running a utility in a developing country was a relatively simple exercise in engineering and economics. Utilities started with a forecast of expected load and then planned, constructed, and operated resource facilities to meet that load. But the double digit inflation in developing countries magnified the cost of new facilities of any kind and caused operating costs to escalate rapidly. The lack of funds and technical know-how further aggravated the situation. Furthermore, when a new generating plant is brought on line, it is followed by a rate increase for the customer. Because of this, of late it has been stressed that utility objectives must be more sensitive to satisfying consumer needs at the lowest possible cost. These factors created the need for alternative actions to be taken and have compelled utility management to reassess its long term objectives and to look at new innovative operating strategies to meet the desired demand without affecting economic activity. Load management seems to provide a viable contribution in an attempt. to achieve the financial and customer objectives of many utilities. This study discusses the various issues of load management with respect to the case of Nepal. The study encompasses the commercial and industrial sectors and emphasizes the Direct Load Control (DLC) technique . The report is divided into six parts: Chapter One gives an introduction and outlines the problems and scope of the study; Chapter Two discusses the theoretical consideration of load management; Chapter Three gives a general background of Nepal's power system; Chapter Four outlines the development of load management and their effects on the power system; programs Chapter Five deals with the costs and benefits of implementing r.t particular load management program and Chapter Six concludes with the findings of the study.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Electric power-plants -- Nepal -- Load; Electric power consumption -- Nepal -- Forecasting